Late preterm and very preterm infants differ in the acquisition time and quantity of reaches with grasping at reaching onset: an exploratory study - França, Andressa Lagoa Nascimento; Teruia, Priscila Maier; de Oliveira Arguelho, Amanda; Tudella, Eloisa; Soares-Marangoni, Daniele Almeida (Frontiers in Psychology, 2023)
Introduction The onset of manual reaching allows the expansion of the infant’s interaction with the environment. When born preterm, infants become vulnerable to problems in the development of reaching. However, it is still unknown whether there are differences in reaching according to the degree of prematurity. Objective This study aimed to explore the differences in reaching acquisition and behavior between late preterm and very preterm infants, as well as whether age and clinical variables influence the results. Method This is an exploratory, comparative, observational study. In total, 24 infants were included soon after reaching onset; 12 infants were born late preterm (35.55 ± 0.67 gestational weeks) and 12 very preterm (30.60 ± 0.05 gestational weeks). Infants were placed in a baby seat, and a toy was placed at a reachable distance for 2 min. Reaching behavior was the primary variable; birth weight and length of hospital stay were secondary variables. Results The age of reaching onset was higher in the very preterm group. The proportion of reaches with grasping was higher in the late preterm group. These differences were affected by the lower birth weight and longer length of hospital stay in the very preterm group. The proportions of proximal and distal adjustments did not differ between groups. Conclusion Very preterm infants presented disadvantages in the acquisition time and the number of reaches with grasping, but not in the proportions of proximal and distal adjustments of reaching, relative to late preterm infants. Group differences were influenced by clinical variables.